Halogenated flame retardants in mangrove sediments from the Pearl River Estuary, South China: Comparison with historical data and correlation with microbial community. (July 2019) - Hu, Yongxia; Pei, Nancai; Sun, Yuxin; Xu, Xiangrong; Zhang, Zaiwang; Li, Huawei; Wang, Weiwei; Zuo, Linzi; Xiong, Yanmei; Zeng, Yanhong; He, Kehong; Mai, Bixian
Abstract: Polybrominated diphenyl ethers (PBDEs), decabromodiphenyl ethane (DBDPE), 1, 2-bis(2, 4, 6-tribromophenoxy)ethane (BTBPE), tetrabromobisphenol A (TBBPA), hexabromocyclododecane (HBCDD) and dechlorane plus (DP) were measured in sediments collected from three mangrove wetlands of the Pearl River Estuary (PRE) in South China. This study aims to investigate the distribution of these halogenated flame retardants (HFRs) and the correlations between HFRs and microbial community structure in mangrove sediments. Concentrations of PBDEs, DBDPE, BTBPE, TBBPA, HBCDD and DP in mangrove sediments ranged from 6.97 to 216.1, 3.70–26.0, 0.02–0.73, 0.02–37.5, 0.44–127.5 and 0.07–2.23 ng/g dry weight, respectively. Higher levels of PBDEs, BTBPE, HBCDD and DP were observed in sediments from Futian mangrove wetland of Shenzhen, the only nature reserve located in the downtown of China. The highest concentration of TBBPA found in mangrove sediments from Guangzhou was proximate to a ferry terminal and a dockyard where TBBPA is widely used in the coatings. PBDEs were the predominant HFRs in mangrove sediments, with an average contribution of 63.0%. Mangrove sediments from Guangzhou and Zhuhai showed an enrichment of (−)- α -HBCDD, (−)- β -HBCDD and (−)- γ -HBCDD. Concentrations of HFRs in mangrove sediments from Guangzhou increased significantly from 2012 to 2015, which was probably due to the establishment and rapid development of Nansha Free Trade Zone of Guangzhou. Redundancy analysis showed that HFRs may cause a shift of microbial community structure in mangrove sediments and the variations were significantly correlated with TBBPA, syn -DP and BTBPE. Graphical abstract: Image 1 Highlights: HFRs and microbial community structure were determined in mangrove sediments. Mangrove sediments from Shenzhen had higher levels of PBDEs, BTBPE, HBCDD and DP. HFRs levels in Guangzhou mangrove sediments increased from 2012 to 2015. Three mangrove wetlands had distinct distribution patterns of non-PBDE HFRs. HFRs in mangrove sediments had significant relationships with the PLFA profiles.